2016
DOI: 10.1186/s12863-016-0449-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in EGFR pathways in mouse kidney-potential impact on the immune system

Abstract: BackgroundEpidermal growth factor receptor (Egfr) has been the target of several drugs for cancers. The potential gender differences in genes in the Egfr axis have been suggested in humans and in animal models. Female and male mice from the same recombinant inbred (RI) strain have the same genomic components except the sex difference. A population of different RI mouse strains allows to conduct precise analysis of molecular pathways and regulation of Egfr between female and male mice.MethodsThe whole genome ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In the gender subgroup analysis of the current study, the female EGFR mutation population showed a higher distribution frequency of LncRNA H19 SNP rs217727 as well as rs2107425 but a lower distribution frequency of LncRNA H19 SNP rs2839698. The difference of LncRNA H19 SNP distribution between the two gender subgroups may be due to the existence of expression quantitative trait loci which lead to gender-difference expression of LncRNA inter chr4 3011 in mice [ 46 ] and the possible difference function of EGFR pathway between gender, which is found in the kidney mouse [ 47 ], may also cause such gender difference as the expression of LncRNA PACER in periodontitis [ 48 ]. Since the LncRNA H19 SNP rs217727 was related to lung cancer development [ 45 ] and LncRNA H19 SNP rs2107425 was correlated to shorter metastasis-free survival [ 49 ], it may be reasonable for the similar condition in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In the gender subgroup analysis of the current study, the female EGFR mutation population showed a higher distribution frequency of LncRNA H19 SNP rs217727 as well as rs2107425 but a lower distribution frequency of LncRNA H19 SNP rs2839698. The difference of LncRNA H19 SNP distribution between the two gender subgroups may be due to the existence of expression quantitative trait loci which lead to gender-difference expression of LncRNA inter chr4 3011 in mice [ 46 ] and the possible difference function of EGFR pathway between gender, which is found in the kidney mouse [ 47 ], may also cause such gender difference as the expression of LncRNA PACER in periodontitis [ 48 ]. Since the LncRNA H19 SNP rs217727 was related to lung cancer development [ 45 ] and LncRNA H19 SNP rs2107425 was correlated to shorter metastasis-free survival [ 49 ], it may be reasonable for the similar condition in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] It has been reported that there are differences in the molecular pathways of EGFR in the kidney and liver between female and male mice. Most importantly, NRP1 is the co-receptor of epidermal growth factor receptor (EGFR), which can control EGFR signaling and tumor growth.…”
mentioning
confidence: 99%
“…Most importantly, NRP1 is the co-receptor of epidermal growth factor receptor (EGFR), which can control EGFR signaling and tumor growth. [3][4][5] It has been reported that there are differences in the molecular pathways of EGFR in the kidney and liver between female and male mice. Many of sex differential expressed genes are related to hormone metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, P-EGF-Cy7 did not exhibit any significant tumor accumulation, while in vitro results showed a relatively strong interaction with EGFR. However, a strong accumulation of P-EGF-Cy7 in liver and kidney was observed at all time intervals, which may be due to the cross-reactivity of the human EGF [27] with murine EGFR overexpressed in liver [28] and kidney of mice [29]. No significant accumulation of GE11 and mAb cetuximab in liver and kidney was observed, thus proving no or very low cross-reactivity with mouse EGFR.…”
Section: Tumor Accumulation Based On Molecular Weight Of Conjugates Vmentioning
confidence: 87%